Effective anger management for children and youth the manual and workbook - Ooi, Yoon Phaik (World Scientific Pub. Co., 2015)
The Effective Anger Management for Children and Youth manual and workbook are specially designed for teachers, counsellors, social workers, psychologists and other mental health professionals who assist in various capacities in working with children who exhibit anger and aggression problems. The ideas, materials, suggested activities and games included in this resource book are applicable to both primary and secondary school children. The purpose of this resource book is to provide practical strategies divided into 12 lessons that teachers and mental health professionals can implement; it is a "how to" book on enhancing children's emotion management, problem-solving and social skills